(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this study was aimed at determine students’ writing skills using the peer group roundtables technique in learning English for class VIII B SMP Kartika XX-2 Makassar. The type of research used in this study was classroom action research (CAR), which consisted of two cycles and two meetings in each cycle. Research procedures include planning, action, observation, and reflection. The subjects of this study amounted to 24 students. The research instruments were tests, observation sheets, and questionnaires using qualitative and quantitative descriptive. The results of this study showed that the average score on the pre-test was 60,2 and there were 29,2 (7 students) who scored ≥75, the average score on the first cycle test was 71,7, and there were 45,8% (11 students) who scored ≥75, the average score in the second cycle test was 80,3, and there were 100% (24 students) who scored ≥75, this shows that the scores and averages in cycle II were better from the first cycle. Based on tests, observation sheets, questionnaires, and documentation, improvement shows that students can be active, enthusiastic, diligent, courageous, and passionate, and students can write descriptive paragraphs easily through the peer group roundtables technique. It was found that teaching writing descriptive paragraphs through the peer roundtables technique could improve students’ writing skills. The students’ responded through the questionnaire the researcher could conclude that the students were responsive and able to improve the students in learning writing skills by using the peer group roundtables technique.